2005
DOI: 10.1111/j.1540-8191.2005.200450.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Closure of Combined Symptomatic Patent Foramen Ovale and Atrial Septum Aneurysm for Prevention of Recurrent Cerebral Emboli

Abstract: Background: Patients with patent foramen ovale (PFO) have an undefined but certainly considerable risk of repeated cerebral ischemia due to paradoxical embolism. Especially, if a cerebrovascular event has already occurred and the combination with an atrial septum aneurysm (ASA) is present this risk increases tremendously. The aim of this study was to demonstrate that surgical closure of PFO in combination with an ASA is safe and useful in preventing recurrent strokes. Methods: Ten patients with previous cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, recent studies reported a higher re-event rate under anti-platelet therapy with aspirin and an advantage for interventional closure [22,36]. Surgery as an alternative treatment showed a wide range of re-event rates from zero to 19.5% within 18 months [37][38][39][40]. In contrast, the periinterventional rate of severe complications in percutaneous closure techniques is very low.…”
Section: Discussionmentioning
confidence: 91%
“…However, recent studies reported a higher re-event rate under anti-platelet therapy with aspirin and an advantage for interventional closure [22,36]. Surgery as an alternative treatment showed a wide range of re-event rates from zero to 19.5% within 18 months [37][38][39][40]. In contrast, the periinterventional rate of severe complications in percutaneous closure techniques is very low.…”
Section: Discussionmentioning
confidence: 91%
“…For secondary prevention, surgical closure of the PFO and percutaneous transcatheter closure of the foramen ovale have been developed, but their benefits have not been established [91][92][93][94][95]. The relationship between PFOs and migraine has been pointed out, and percutaneous transcatheter closure of the foramen ovale has been reported to improve migraines 93 (IIb).…”
Section: Evidencementioning
confidence: 98%
“…The major disadvantage of surgical closure is that it requires thoracotomy and cardiopulmonary bypass. There have been several nonrandomized limited series addressing safety and efficacy [6,20,21]. Although peri-operative mortality is minimal, morbidity includes atrial fibrillation, pericardial drainage for effusion, repeat surgery for exploration for bleeding source, wound infection, and postpericardiotomy syndrome.…”
Section: Treatment To Prevent Stroke In Patients With Pfomentioning
confidence: 99%